Ptophobia: the fear of falling in elderly people. - Gai, Juliana (2009)
Falling is a serious problem for the elderly which consequences--fractures, other lesions and the fear of falling--may result in auto-restrictions in daily living activities, producing immobility and accelerating the physical decline associated with aging. The ptophobia (phobic fear of falling) is characterized by an out-of-control fear of walking, even without locomotion alteration, loss of self-esteem and social isolation. Interventions for the prevention and treatment of the falling fear in the elderly are very important to assure a good quality of life. Psychotherapy and physical rehabilitation have been related as ways of treatment of ptophobia in the elderly.